2002
DOI: 10.4049/jimmunol.168.10.5233
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-Mediated Monitoring of Tissue Well-Being Via Detection of Soluble Heparan Sulfate by Toll-Like Receptor 4

Abstract: Perturbations to the well-being of tissues in plants and invertebrates generate fragments of endogenous molecules that are recognized by innate immune receptors. Vertebrates have homologous receptors on specialized cells such as dendritic cells, but whether these receptors respond to fragments of endogenous molecules is not known. We tested the idea that Toll-like receptors on dendritic cells might recognize polysaccharide fragments of heparan sulfate proteoglycan. Dendritic cells were found to mature in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
370
1
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 591 publications
(391 citation statements)
references
References 68 publications
(74 reference statements)
6
370
1
11
Order By: Relevance
“…These include HMGB1 76 31, uric acid 77 , some HSPs 78 79, some defensins [G] 80 , hyaluronic acid 81 , heparan sulfate 82 , and some fragments of extracellular matrix proteins 70 . Whereas this data may well be correct, caution is warranted because TLRs can be stimulated by microbial contaminants that are easily introduced during the purification of molecules.…”
Section: Receptors For Dampsmentioning
confidence: 99%
“…These include HMGB1 76 31, uric acid 77 , some HSPs 78 79, some defensins [G] 80 , hyaluronic acid 81 , heparan sulfate 82 , and some fragments of extracellular matrix proteins 70 . Whereas this data may well be correct, caution is warranted because TLRs can be stimulated by microbial contaminants that are easily introduced during the purification of molecules.…”
Section: Receptors For Dampsmentioning
confidence: 99%
“…Out of 13 currently known TLR members (11 in humans), TLR4 is believed to initiate inflammation and tissue injury by responding to both bacterial endotoxin (lipopolysaccharide) and multiple endogenous ligands, including hyaluronic acid, heparin sulfate, fibrinogen, beta defensin, and heat-shock proteins. 10,11 We and others have reported that TLR4 complex is involved in the initiation of IRI. [12][13][14][15][16] Indeed, we found that livers in TLR4 knockout (KO) but not TLR2 KO mice were resistant to IRI and associated intrahepatic inflammation.…”
mentioning
confidence: 97%
“…Endogenous ligands are released upon normal cell turnover and stressful events and are likely to be abundant in the synovial compartment. The pivotal role of endogenous ligands was substantiated by the finding that such signals lead to primary immune responses under conditions of cell stress and precipitate autoimmunity in the presence of self antigens (28)(29)(30)(31). Therefore, endogenous ligands are considered to be natural initiators of autoimmunity.…”
mentioning
confidence: 99%